The Influence of Profitability, Capital Structure, and Company Size on Dividend Policy Moderated by the Independent Board of Commissioners - Affandi, Aryo Juliansyah; Kusmayadi, Iwan (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to examine the influence of profitability, capital structure, and company size on dividend policy, considering the role of independent board of commissioners as a moderation variable. The object of the study is focused on manufacturing companies listed on the Indonesia Stock Exchange for the 2020–2024 period. The approach used is quantitative with the Moderated Regression Analysis (MRA) analysis method, based on 380 observational data from 76 selected companies using purposive sampling techniques. The findings of the study show that profitability has a significant negative impact on dividend policy, but the capital structure does not show a significant influence. On the other hand, the size of the company has a positive and significant effect. The independent board of commissioners does not moderate the influence of profitability or capital structure, but acts as a negative moderator in the relationship between company size and dividend policy.